On‐surface synthesis of porous graphene nanoribbons containing nonplanar [14]annulene pores. Issue 12 (18th February 2022) - Ajayakumar, M. R.; Di Giovannantonio, Marco; Pignedoli, Carlo A.; Yang, Lin; Ruffieux, Pascal; Ma, Ji; Fasel, Roman; Feng, Xinliang
Abstract: The precise introduction of nonplanar pores in the backbone of graphene nanoribbon represents a great challenge. Here, we explore a synthetic strategy toward the preparation of nonplanar porous graphene nanoribbon from a predesigned dibromohexabenzotetracene monomer bearing four cove‐edges. Successive thermal annealing steps of the monomers indicate that the dehalogenative aryl‐aryl homocoupling yields a twisted polymer precursor on a gold surface and the subsequent cyclodehydrogenation leads to a defective porous graphene nanoribbon containing nonplanar [14]annulene pores and five‐membered rings as characterized by scanning tunneling microscopy and noncontact atomic force microscopy. Although the C–C bonds producing [14]annulene pores are not achieved with high yield, our results provide new synthetic perspectives for the on‐surface growth of nonplanar porous graphene nanoribbons. Abstract :